2017
DOI: 10.5130/ijcre.v10i1.5151
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the empowerment expectation: Learning, alienation and design possibilities in community-university research

Abstract: As community-university partnerships have become mainstream, researchers have argued that these approaches have the potential to be transformative, supporting community learning and creating capacity for community development. While this remains the dominant narrative of community research, some researchers have questioned the impacts of community research on frontline community, or peer, researchers who represent partnerships in their communities. These studies complicate the narrative, suggesting that learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Evidence of this broadened role for higher education in practice is the global change movement by universities to take an active role in social change projects through international organizations such as the Global University Network for Innovation, the Talloires Network of Engaged Universities, UNESCO, and an array of world regional and national organizations, in which scholars collaborate with practitioners and communities to improve social conditions (Curnow, 2017;Escrigas, et al, 2013;Hall & Tandon, 2020;Hoyt & Newcomb Rowe, 2017). There are many examples of these university-community partnerships for social change involving economic justice, health, poverty, and sustainability (Hall, et al, 2013;Hall, Tandon, & Tremblay, 2015;Tandon, et al, 2016).…”
Section: New Directions In Higher Education and Critical Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of this broadened role for higher education in practice is the global change movement by universities to take an active role in social change projects through international organizations such as the Global University Network for Innovation, the Talloires Network of Engaged Universities, UNESCO, and an array of world regional and national organizations, in which scholars collaborate with practitioners and communities to improve social conditions (Curnow, 2017;Escrigas, et al, 2013;Hall & Tandon, 2020;Hoyt & Newcomb Rowe, 2017). There are many examples of these university-community partnerships for social change involving economic justice, health, poverty, and sustainability (Hall, et al, 2013;Hall, Tandon, & Tremblay, 2015;Tandon, et al, 2016).…”
Section: New Directions In Higher Education and Critical Spacesmentioning
confidence: 99%
“…Second, universities that have significant successful experience working hand-in-hand to empower communities to design and implement social change using deliberative principles could be identified. Third, the global change movement involving universities, such as the Global University Network for Innovation, the Talloires Network of Engaged Universities, and an array of international organizations and foundations could be tapped for their expertise and support (Curnow, 2017;Escrigas, et al, 2013;Hall & Tandon, 2020;Hoyt & Rowe, 2017).…”
Section: Conclusion: Critical Spaces Deliberation and Community Engag...mentioning
confidence: 99%
“…I also understand my responsibility to use my privilege and power as a doctoral student researcher to facilitate change. It would be highly unrealistic for me to expect my co-researchers to complete the action piece of our project, as expected by Curnow (2017), on their own. Another way I was able to fulfill my responsibility as a supportive researcher was listening to the voices and stories of my peers.…”
Section: Social Locationmentioning
confidence: 99%
“…However, studies of community-university partnerships have also identified negative results. For example, Curnow (2017) writes about community research projects that have been experienced by peer researchers as disempowering and alienating. Levkoe (2017) highlights research that speaks to an array of barriers and consequences community partners can face within community campus engagements.…”
Section: Strengths and Limitations Of Community-university Collaboratmentioning
confidence: 99%
“…Levkoe (2017) highlights research that speaks to an array of barriers and consequences community partners can face within community campus engagements. Some examples include the need for addressing knowledge hierarchies (Anderson and McLachlan 2016), and reconciling the tensions between knowledge production and action-oriented social change (Warren et al 2018;Curnow 2017;Stoecker and Tryon 2009), including responding to the pull between developing accessible resources valued by community partners and the production of publications for academic audiences (Watson-Thompson 2015). Failure to address these challenges can prevent an overt focus on justice 4 in practice (Da Cruz 2018), which can in turn re-inscribe the power discrepancies that community-engaged scholars often intend to disrupt and change.…”
Section: Strengths and Limitations Of Community-university Collaboratmentioning
confidence: 99%